Postexercise cold water immersion benefits are not greater than the placebo effect - Broatch, J. R.; Petersen, A.; Bishop, D. J. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Despite a general lack of understanding of the underlying mechanisms, cold water immersion (CWI) is widely used by athletes for recovery. This study examined the physiological merit of CWI for recovery from high-intensity exercise by investigating if the placebo effect is responsible for any acute performance or psychological benefits.